empty pericarp4 encodes a mitochondrion-targeted pentatricopeptide repeat protein necessary for seed development and plant growth in maize. - Gutiérrez-Marcos, J; Dal Prà, M; Giulini, A; Costa, L; Gavazzi, G; Cordelier, S; Sellam, O; Tatout, C; Paul, W; Perez, P; Dickinson, H; Consonni, G (2007)
The pentatricopeptide repeat (PPR) family represents one of the largest gene families in plants, with >440 members annotated in Arabidopsis thaliana. PPR proteins are thought to have a major role in the regulation of posttranscriptional processes in organelles. Recent studies have shown that Arabidopsis PPR proteins play an essential, nonredundant role during embryogenesis. Here, we demonstrate that mutations in empty pericarp4 (emp4), a maize (Zea mays) PPR-encoding gene, confer a seed-lethal phenotype. Mutant endosperms are severely impaired, with highly irregular differentiation of transfer cells in the nutrient-importing basal endosperm. Analysis of homozygous mutant plants generated from embryo-rescue experiments indicated that emp4 also affects general plant growth. The emp4-1 mutation was identified in an active Mutator (Mu) population, and cosegregation analysis revealed that it arose from a Mu3 element insertion. Evidence of emp4 molecular cloning was provided by the isolation of four additional emp4 alleles obtained by a reverse genetics approach. emp4 encodes a novel type of PPR protein of 614 amino acids. EMP4 contains nine 35-amino acid PPR motifs and an N-terminal mitochondrion-targeted sequence peptide, which was confirmed by a translational EMP4-green fluorescent protein fusion that localized to mitochondria. Molecular analyses further suggest that EMP4 is necessary to regulate the correct expression of a small subset of mitochondrial transcripts in the endosperm.